2010
DOI: 10.1186/1749-8090-5-20
|View full text |Cite
|
Sign up to set email alerts
|

The need for intra aortic balloon pump support following open heart surgery: risk analysis and outcome

Abstract: BackgroundThe early and intermediate outcome of patients requiring intraaortic balloon pump (IABP) was studied in a cohort of 2697 adult cardiac surgical patients.Methods136 patients requiring IABP (5.04%) support analysed over a 4 year period. Prospective data collection, obtained.ResultsThe overall operative mortality was 35.3%. The "operation specific" mortality was higher on the Valve population.The mortality (%) as per time of balloon insertion was: Preoperative 18.2, Intraopeartive 33.3, postoperative 58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
34
3
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 21 publications
9
34
3
8
Order By: Relevance
“…In our study, IABP was used in 8.1% of our patients, which is similar to results reported in other studies [10,11]. Although some studies have shown that survival at follow-up was better for receiving preoperative IABP as compared to intra- or postoperative IABP [1,7,12,13], other studies have shown that the use of prophylactic IABP in high-risk patients did not lead to any survival advantage compared with the use of intraoperative or postoperative IABP [10,11].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, IABP was used in 8.1% of our patients, which is similar to results reported in other studies [10,11]. Although some studies have shown that survival at follow-up was better for receiving preoperative IABP as compared to intra- or postoperative IABP [1,7,12,13], other studies have shown that the use of prophylactic IABP in high-risk patients did not lead to any survival advantage compared with the use of intraoperative or postoperative IABP [10,11].…”
Section: Discussionsupporting
confidence: 91%
“…In a failing heart, IABP represents an option of left ventricular support. The need for IABP especially in a high risk valve population is associated with early unfavorable outcome [15]. On the contrary, our study did not demonstrate a benefi t from IABP use.…”
Section: Discussioncontrasting
confidence: 84%
“…It was developed by the researcher after reviewing the related literature . (2,(6)(7)(8)(9)(10) this tool was used to assess the baseline nurse's practice about IABP .It was consist of fourty steps covering the practical aspects which focus on nursing preparation and initiation of IABP Therapy (steps from 1-11),immediately nursing care(steps from 12-14), care of central lumen(steps from [15][16][17][18][19][20], general assessment guidelines (steps from 21-26) , and nursing consideration during weaning and IABP removal (steps from 27-40). Scoring system for nurse's practice: The total score for all steps were 40 and every step was evaluated as follows; correctly done was scored (2), in-correctly done was scored (1) and not done was scored (0).…”
Section: Methodsmentioning
confidence: 99%